2006
DOI: 10.1142/s0217751x06034318
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating Universe as Window for Extra Dimensions

Abstract: Homogeneous cosmological solutions are obtained in five dimensional space time assuming equations of state p = kρ and p 1 = γρ where p is the isotropic 3 -pressure and p 1 , that for the fifth dimension. Using different values for the constants k and γ many known solutions are rediscovered. Further the current acceleration of the universe has led us to investigate higher dimensional gravity theory, which is able to explain acceleration from a theoretical view point without the need of introducing dark energy b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 34 publications
(43 reference statements)
2
25
0
Order By: Relevance
“…Thus, one concludes that if the 3D scale factor is undergoing accelerated expansion in the late universe, when the approximations of this appendix are valid, then the higher-dimensional scale factor can not be dynamically compactifying. A similar result was found in [11].…”
Section: Figsupporting
confidence: 89%
See 3 more Smart Citations
“…Thus, one concludes that if the 3D scale factor is undergoing accelerated expansion in the late universe, when the approximations of this appendix are valid, then the higher-dimensional scale factor can not be dynamically compactifying. A similar result was found in [11].…”
Section: Figsupporting
confidence: 89%
“…As η 1 is strictly positive The approximations of this appendix, which give rise to the solutions of (A5) and (A9), yield a generalized treatment of the case of dynamical compactification, which has been previously studied elsewhere (see [9][10][11]). There, the higherdimensional scale factor was assumed to dynamically evolve through a relation of the form of (A9), where n was an arbitrary parameter constrained only by the relation n > 0.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In [21] Peng et al extend the direct quantum approach to the FRW cosmology from 4D to 5D and obtained a Hamiltonian formulation for a wave like 5D FRW cosmology. In [22] Panigrahi et al have shown a scenario in homogeneous 5D space time which behave a decelerating expansion in the early epoch along with an accelerating situation at the present line without introducing any external quintessence-like scalar field in the presence of extra dimension.…”
mentioning
confidence: 99%